2016
DOI: 10.1038/srep24933
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin stimulates autophagic degradation of phosphorylated tau via the activation of TFEB and Nrf2 transcription factors

Abstract: The neuronal accumulation of phosphorylated tau plays a critical role in the pathogenesis of Alzheimer’s disease (AD). Here, we examined the effect of fisetin, a flavonol, on tau levels. Treatment of cortical cells or primary neurons with fisetin resulted in significant decreases in the levels of phosphorylated tau. In addition, fisetin decreased the levels of sarkosyl-insoluble tau in an active GSK-3β-induced tau aggregation model. However, there was no difference in activities of tau kinases and phosphatases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 48 publications
(85 reference statements)
2
77
0
Order By: Relevance
“…We note that autophagy activity was significantly reduced when compared to controls. A previous study has shown that FST promoted autophagic degradation of phosphorylated tau via the activation of TFEB and Nrf2 transcription factors (Kim et al, 2016), suggesting that FST exerts pro-autophagy effects. However, another study has also shown that FST exerts autophagy repressing effects (Yen et al, 2017) at doses < 20 µM in tunicamycin-mediated cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We note that autophagy activity was significantly reduced when compared to controls. A previous study has shown that FST promoted autophagic degradation of phosphorylated tau via the activation of TFEB and Nrf2 transcription factors (Kim et al, 2016), suggesting that FST exerts pro-autophagy effects. However, another study has also shown that FST exerts autophagy repressing effects (Yen et al, 2017) at doses < 20 µM in tunicamycin-mediated cells.…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study, we showed that FST alleviates hepatic lipid metabolism through activation of the SIRT1 pathways (Liou et al, 2018). Similarly, FST has been observed to induce autophagy in multi cancers like breast cancer, oral cell carcinoma, and pancreatic cancer (Yang et al, 2012;Kim et al, 2016;Klimaszewska-Wisniewska et al, 2016;Jia et al, 2019;Park et al, 2019). However, the autophagy effects of FST on liver injury are still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…To test the ability of optically induced transgene expression to clear p-Tau, we chose TFEB, which is a well-established regulator of autophagy, and previously implicated in clearing tau via constitutive activation [29,30,53,54]. As a first step, we decided to confirm whether TFEB can clear p-Tau and determine whether TFEB can target multiple forms of p-Tau via autophagic flux in neuronal cells.…”
Section: Tfeb Clears Multiple Forms Of Pathological Tau With Equal Efmentioning
confidence: 99%
“…This compound was able to induce autophagy by simultaneously promoting the activation and nuclear translocation of both TFEB and NRF2, along with some of its target genes. This response was prevented by TFEB or NRF2 silencing [125]. Bott and colleagues reported beneficial effects of a simultaneous NRF2, NRF1 and HSF1 activator on protein toxicity in spinal and bulbar muscular atrophy, a neurodegenerative disorder caused by expansion of polyglutamine-encoding CAG repeats in which protein aggregates are present [126].…”
Section: Promising Therapeutic Potential For Nrf2 In Proteinopathiesmentioning
confidence: 99%